2009
DOI: 10.4085/1062-6050-44.2.165
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Method for Identifying Scapular Dyskinesis, Part 2: Validity

Abstract: Context: Although clinical methods for detecting scapular dyskinesis have been described, evidence supporting the validity of these methods is lacking.Objective: To determine the validity of the scapular dyskinesis test, a visually based method of identifying abnormal scapular motion. A secondary purpose was to explore the relationship between scapular dyskinesis and shoulder symptoms.Design: Validation study comparing 3-dimensional measures of scapular motion among participants clinically judged as having eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
138
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(152 citation statements)
references
References 42 publications
2
138
0
12
Order By: Relevance
“…First, scapular function and motion were not assessed on these players while performing their sport-specific movements such as throwing or pitching. Instead, a clinical method of scapular evaluation was used that involved elevation of the shoulder in the scapular plane using a 2-pound weight as has been advocated and studied elsewhere in the clinical and experimental literature [8,12,18,19]. Second, the use of video recording and capture of the upper extremity movements rather than live evaluation may have limited the interpretation of scapular outline and full appreciation of some aspects of human scapular motion that are better captured with live observation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, scapular function and motion were not assessed on these players while performing their sport-specific movements such as throwing or pitching. Instead, a clinical method of scapular evaluation was used that involved elevation of the shoulder in the scapular plane using a 2-pound weight as has been advocated and studied elsewhere in the clinical and experimental literature [8,12,18,19]. Second, the use of video recording and capture of the upper extremity movements rather than live evaluation may have limited the interpretation of scapular outline and full appreciation of some aspects of human scapular motion that are better captured with live observation.…”
Section: Discussionmentioning
confidence: 99%
“…They identified satisfactory reliability using this scapular classification system in overhead athletes. Tate et al [18] performed an additional study to validate the scapular classification system used in the study by McClure et al [12] using 66 of the same 142 subjects clinically analyzed in the McClure et al study. Using threedimensional electromagnetic kinematic testing, Tate et al [18] revealed less scapular upward rotation and less clavicular elevation in subjects classified with obvious dyskinesis compared with those classified with normal scapular motion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations